Repetição e Coordenação - Camacho, Roberto Gomes [UNESP] (1998)
Based on the principle that the cognitive motivation pervades all levels of the grammar of a language, the basic aim of this paper is to explore the hypothesis that the coordenative processes of conjunction and disjunction result from a perceptual-cognitive transference of common mechanisms of repetition. By means of a multifunctional analysis of coordination, it is showed that term conection is the model that activates sentence conection processes at which additive and alternative junctives establish content relations at ideational level, and epistemic and speech act relations at the interactional level.